As relações entre força quantificacional e posição sintática: uma análise sintático-semântica dos verbos existenciais - Emerson Gonçalves de Souza (2023)
In this dissertation, we take as our object of study the relations between quantificational strength and syntactic position of a quantifier when combined with existential verbs, that is, as arguments in sentences formed from existential verbs. Heim and Kratzer (1998) postulate the inability of strong quantifiers to occupy an argument position of existential verbs. This is due to the fact that existential verbs assert the existence of the nominal element that accompanies them, while strong quantifiers presuppose the existence of the nominal element they refer to (HEIM; KRATZER, 1998). There is, therefore, an incompatibility between presupposition of existence and assertion of existence, nullifying forces. However, even with such semantic limitations, in Brazilian Portuguese (BP) there is a possibility that a strong quantifier occurs in an argument position of an existential verb (VIOTTI, 2002). To explain these occurrences, we hypothesize that the movement of quantifier expressions to the pre-verbal position in the sentence, tense, and the addition of modifiers are elements that license the occurrence of strong elements in sentences with existential verbs. Based on this hypothesis, the research aimed to contribute to the study and grammatical understanding of BP, comparing the syntactic structures of the analyzed sentences and relating these occurrences to strong and weak quantifiers, in order to verify a possible systemic relationship between the position of the argument and the type of quantifier that heads the argument. We analyzed the existential verbs existir, haver, ter, abundar (OLIVEIRA, 2020) in combination with strong quantifiers/determiners todos, cada, and a maioria de and also in combination with weak quantifiers poucos, muitos and numerals. The analysis resulted in a systematic correlation between syntactic position and quantificational strength, and we also observed the influence of tense and the inclusion of modifiers, as hypothesized. The data indicates that the strong quantifier and the referred nominal element occupy the pre-verbal position when occurring with existential verbs. This displacement phenomenon seems to be facilitated even further when associated with the past tense and delimited by diverse adjuncts. From this result, we propose that situations of conflict between presupposition of existence and assertion of existence are derived from the incidence of these two factors on the same referent, and that, by moving the strong quantifier and the referred nominal element to the pre-verbal position of the sentence, a differentiation occurs between the referent of the presupposition and the referent of the assertion, that is, there is a presupposition of existence of an element different from that about which existence is asserted. The adjuncts and past tense enable this differentiation, since they contribute to a subset effect in the sentence, so that the presupposed existence refers to a determined set, while the assertion of existence occurs over a subset of such a set.